Licensing Contracts: Control Rights and Options - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2014)
Research and development (R&D) collaborations have become very common in many high-tech industries. These collaborations can be challenging to manage because of the high degree of technical and market uncertainty as well as the difficulty in monitoring each other’s effort in research, development and marketing. We investigate how the contract structure, i.e., payment terms and control rights, that governs licensing arrangements between an innovator and a marketer influences the success of such R&D collaboration. Control rights give each of the collaborating parties specific rights in terms of being able to buy back the exclusive rights to a product, or having final say whether or not the product should be launched or discontinued. Our study reveals a counterintuitive result, in that the innovator may, under certain conditions, prefer to grant launch control rights to the marketer. We also find that an option to buy out the innovator, despite limiting the upside potential for the innovator, can generate strong research incentives by creating a significant difference in payoffs between the high- and low-quality outcomes, resulting in an overall benefit. We also show that the nature of the effect of R&D effort on the likelihood of success and quality of the product can have a major influence on how a contract should be structured, and what value can be obtained from it. Finally, we demonstrate that careful allocations of control rights can have a significant influence on the success, quality and profitability of a collaborative R&D venture and provide recommendation on the optimal contract structure based on the R&D project characteristics.